Consumo de sustancias psicoactivas entre adolescentes en conflicto con la ley penal - Morales Córdova, Hugo (2006)
This paper offers a descriptive approximation to some characteristics of the  consumption of alcohol and psychoactive substances in a sample of 1400 adolescents offenders attended by the Penal System Peruvian. Among the main finding is the  demonstration fall a prevalence of the consumption of drugs in general and few cases of addiction; even though there exists a high prevalence of consumption of alcohol. This paper concludes with some recommendations of preventive action on this particular population.